A180 RISK FACTORS FOR INADEQUATE GESTATIONAL WEIGHT GAIN IN PREGNANT PATIENTS WITH INFLAMMATORY BOWEL DISEASES. (4th March 2021) - Tandon, P; Hanna, Y; Cepo, J; Maxwell, C; Huang, V W
Abstract: Background: Patients with inflammatory bowel disease (IBD) are at a risk of inadequate gestational weight-gain (GWG) which in turn may increase the risk of adverse pregnancy outcomes. Aims: To determine the risk factors for inadequate GWG in these patients and to determine the impact on adverse pregnancy outcomes. Methods: Pregnant patients with IBD, both ulcerative colitis (UC) and Crohn's disease (CD), were identified retrospectively at the Mount Sinai Hospital from 2016 to 2020. Total gestational weight-gain (GWG) was calculated as the difference of the weight recorded at time of labor and pre-pregnancy weight. GWG was further stratified into less than adequate, adequate, and more than adequate based on the pre-pregnancy body-mass index and standards set by the U.S. Institute of Medicine. Pregnancy-related outcomes were also recorded for each patient. Disease activity was recorded at each trimester visit and defined by a fecal calprotectin (FCP) > 250 ug/g. Differences in the mean GWG were compared using independent T-test with standard deviations (SD) whereas categorical variables were compared using the Chi-square (x 2 ) test. Results: 71 pregnancies in 71 patients were included (33 UC and 38 CD). Thirteen patients (18.3%) had less than adequate, 23 (32.4%) adequate, and 35 (49.3%) more than adequate GWG. Of the 33 patients with UC, 4 (12.2%) had less than adequate, 15 (45.5%) had adequate, and 14 (42.4%) had more than adequate GWG. Of the 38 patients with CD, 9 (23.7%) had less than adequate, 8 (21.1%) had adequate, and 21 (55.3%) had more than adequate GWG (p=0.07) for CD vs. UC). In those with CD, both fistulizing and stricturing CD phenotypes appeared to be numerically associated with inadequate GWG. Specifically, none of the 13 patients with fistulizing CD had adequate GWG compared to 32.0% (8/25) in those without fistulizing disease (p=0.07). Similarly, only 2/22 (9.1%) of those with stricturing CD had adequate GWG compared to 6/16 (37.5%) in those without stricturing disease (p=0.07). Furthermore, of seven patients with active disease in the first trimester, only one had adequate GWG (14.3%) compared to 37.5% (3/8) of those in clinical remission (p=0.044). Active disease in trimesters two and three was not associated with inadequate GWG. Finally, the mean GWG was higher in those undergoing Cesarean (37.8 kg (SD 14.1) vs. 30.4 kg (SD 10.5), p=0.014)) and emergency Cesarean delivery (43.5 kg (SD 17.6) vs. 31.9 kg (SD 10.7) (p=0.004) compared to vaginal delivery respectively. Conclusions: Patients with CD, but not UC, and those with active disease in the first trimester, are at risk of inadequate GWG during pregnancy. In those with larger GWG, a higher rate of emergency Cesarean birth was noted. Optimal intervention to achieve recommended gestational weight-gains in patients with IBD remains to be determined. Funding Agencies: None